Issues and challenges in the enforcement of psychotropic substances by pharmaceutical enforcement department / Nurul Hayati Bohari - Bohari, Nurul Hayati (2011)
This research is about the study on the law enforcement of Pharmaceutical Enforcement Department (PED) on the issues and challenges in the enforcement of psychotropic substances. The focus on this study is on the illegal supply of psychotropic substances by the medical practitioners. As the one and only agencies in the enforcement on the illegal supply of psychotropic substances, it is very important to make sure the method and approaches to curb the abuses and diversion which lead to drug addicts and crimes been identified. The research was based on official statistic data on psychotropic substances control by PED and investigation and prosecution cases, interviews with relevant officers in PED on the current control approaches on the supply of psychotropic substances and critical analysis on information gathered from library and internet. In the illegal supply of psychotropic substances, the medical practitioners prone to unlawful practices such as without or improper treatment (doctor shopping), overprescribe, makes compounding, improper records, improper storage, improper labeling and makes false documentation or declaration. The weaknesses of the PED are because the lack of information, difficulty in getting cooperation from the medical practitioner in the investigation cases and insufficient legislation such as definition of terms and the punishment. Hence, in this study found that the crime happened absolutely because of the medical practitioner is only the authorized person to prescribe and dispensed the psychotropic substances. Thus, there is a need to improve the laws, the enforcement approaches such as established an academy for PED, educating the medical practitioners and the policy approaches in psychotropic substances control related to medical practitioners such as dispensing separation, licensing the medical practitioner purchase and supply the psychotropic substance and established prescription and dispensing computerized system.